A Self-Modeling Intervention for High School Students with Public Speaking Anxiety - Rickards-Schlichting, Kristine A.; Kehle, Thomas J.; Bray, Melissa A. (Single-Subject Designs for School Psychologists, 2004)
The study investigated the effectiveness of self-modeling as an intervention for public speaking anxiety. The participants were six high school students with elevated levels of self-reported public speaking anxiety. Students presented public speeches to randomly selected peer audiences. Direct observations measured the behavioral manifestations of public speaking anxiety. In the intervention phase, students viewed self-modeling videotapes that were edited to remove speech dysfluencies and behavioral symptoms of speech anxiety. The self-modeling tapes depicted only adaptive, exemplary behavior with an edited-in audience feature making it appear that the students were producing a fluent speech to an audience of their peers. All of the participants evidenced substantial decreases in behavioral symptoms of speech anxiety and these changes were 48 maintained throughout follow-up. The range of the participants' effect sizes was 2.7 to 4.9. Self-report measures of state anxiety and confidence as a speaker were used to assess additional effects of treatment. For all participants, there were also substantial decreases in self-reported public speaking anxiety and state anxiety from baseline to follow-up. A post-treatment interview revealed high social validity and self-reported generalization of treatment. [Article copies available for a fee from The Haworth Document Delivery Service: 1-800-HAWORTH. E-mail address: <docdelivery@haworthpress.com> Website: <http://www.HaworthPress.com> © 2004 by The Haworth Press, Inc. All rights reserved.]